Концепція побудови сенсорних систем з використанням нанофотонних та наноелектрохімічних технологій - Сніжко, Д. В. (ХНУРЕ, 2021)
Дисертація містить результати теоретичних й експериментальних досліджень, що спрямовані на розробку концепції технологічних засад використання нанофотонних та наноелектрохімічних технологій для створення сенсорних систем. Їхнє застосування дозволяє покращити аналітичні характеристики систем, розширити функціональність, що включає збільшення номенклатури об’єктів, речовин, що можуть досліджуватися. Вперше запропоновано концепцію побудови надшвидкого потенціостату для реалізації високошвидкісних методів електрохімічної аналізу з використанням мікро-, ультрамікро- та нано-електродів, як сенсорів, яка базується на принципах внутришньокаскадних зв’язків, компенсації омічного падіння в модулі перетворення струм-напруга та застосування режиму повторювача на високих частотах для підсилювача, що керує протиелектродом сенсора. Набув подальшого розвитоку метод надшвидкої вольтамперометрії, що включає дослідження використання мікроелектродів та наноелектродів для електрохімічних досліджень. Отримав широкого розвитку метод хемілюмінесценції, що включає розробку нових композицій та застосування нанотехнологічного п’єзоелектричного активатора аналітичної хемілю-мінесцентної реакції. Це дозволило розробити методики визначення біологіч-нозначущих компонентів рідких проб, таких як аскорбінова кислота, суперок-сиддисмутаза, гемін, тирозиназа. Продемонстровано перспективність використання методу електрогенерованої хемілюмінесценції в сенсорних системах, що включало розробку фізико-хімічної моделі процесів взаємодії етилформату з біпиридиновим комплексом рутенію, що описує механізм генерації аналітичного сигналу. Наведено дані та випрацьовані рекомендації з розробки інструментарію для нанофотонних та наноелектрохімічних сенсорних систем. The dissertation contains the results of theoretical and experimental researches directed on development of the concept of technological bases to use nanophotonic and nanoelectrochemical technologies for sensor system design. Their application allows to improve the analytical characteristics of the systems, to expand the functionality, which includes increasing the range of objects, substances that can be studied. For the first time the concept of construction of ultrafast potentiostat for realization of high-speed methods of electrochemical analysis with using micro-, ultra-micro- and nanoelectrodes as sensors is offered, which is based on the principles of intra-stage connections, ohmic drop compensation in current-to-voltage amplifier stage, intro-duction high frequencies compensation feedback to switch on the amplifier in repeater mode to control the counter electrode of the sensor. The method of ultrafast voltam-metry was further developed, which includes research of the use of microelectrodes and nanoelectrodes for electrochemical assays. Optical signal detection instrumenta-tion including devices for ultra-weak light registration were analyzed. It was verified that the metrological characteristic of modern photomultiplier tubes in counting mode stay significant for sensor system, however, the role of CMOS photodetector is in-creasing in a portable and miniature sensor systems. The design and fabrication method of a microelectrode were proposed for the first time, that includes the sleeve as a technological element that provides a combination of conductors in the electrode case. The design and fabrication method of ultramicroelectrode were proposed for the first time, that includes an additional technological process of the electrode end shaping to obtain working electrode surface of submicron and nanometer level by pulling the working end, which is molten. Samples of microelectrodes with Ø6 μm glassy carbon material, with Ø25 μm gold working disk electrode surface, and Ø500 nm gold ul-tramicroelectrodes were fabricated accordingly to proposed fabrication methods. The method of chemiluminescence received further development that includes the devel-opment of new chemical compositions and sonication actuators to conduct analytical reaction in sensor system. For the first time the concept of building a sensor system on the principle of "point-of-care testing", which includes the use of nanotechnological piezoelectric actuator of the analytical chemiluminescent reaction. It allows to develop new analytical chemiluminescent technologies for determine the biologically signifi-cant components of liquid samples, such as ascorbic acid, superoxide dismutase, hemin, tyrosinase. The prospects of electrogenerated chemiluminescence analysis using in sensor systems have been demonstrated, which includes the development of a physi-cochemical model of the interaction of ethyl formate co-reagent with electrochemi-luminophore - ruthenium bipyridine complex, which describes the mechanism of an-alytical signal generation. The use of the diamond-like film dopped by nitrogen as an electrode material in the technology of electrogenerated chemiluminescence has shown to improve the signal-to-noise ratio for the known ECL composition of the ruthenium bipyridine complex more than 8 times. The new sensor technology for electrode functionalization was developed that is based on carbon nanotubes bonding to substrate by intermediate substance lipoic acid. Perspectives of formation sensitive layer of carbon nanotubes are shown. Experimental sensor system for electrochemical and electrochemiluminescent studies with ultramicroelectrodes was tested in high-speed polarization modes. The use of Langmuir-Blodget technology made it possible to create modified electrodes with binary systems containing luminophore such as ruthenium bipyridyl complex or rubrene. The using of water-insoluble lumi-nophore in aqueous solutions by immobilization of reagent on the electrode for aqueous solution assays is shown. The optimal content of water-insoluble rubrene in the PMMA matrix in the ratio 1: 5 (in recalculation to monomer), 20% take more stable film is maximum of ECL signal generation. The design of several instruments for light detection with different principals were done for application in sensor systems that including colorimeter “C 1001”, apparatus “Spark” for photomultiplier tube (PMT) integration to a measurement system, fast pulse counter “Pulsar” to control operation of PMT in counting mode and propose interface to different measurement system with analog and digital data transfer, analyzer “ELAN-3D” for electrogenerated chemilu-minescent analysis. The recommendations for the development of tools for nanopho-tonic and nanoelectrochemical sensor systems are presented.
Keywords: сенсорна система; біофотоніка; наноелектрохімія; хемілюмінесценція; надшвидкий потенціостат; функціоналізація; програмно-апаратне забезпечення; аналіз речовин; sensor system; biophotonics; nanoelectrochemistry; chemiluminescence; ultrafast potentiostat; functionalization; software and hardware; analysis of substances